AN APPLICATION OF INFORMATION SEEKING ANXIETY SCALE TO A UNIVERSITY LIBRARY: A CASE STUDY AT UNIVERSITY OF PERADENIYA, SRI LANKA - Alahakoon, Champa (PEOPLE: International Journal of Social Sciences, 2017)
Libraries and their users are nervous of falling behind with the rapid rate of technological change. All the forms of academic-related anxiety, and frustrations associated when searching information. Most of the research studies have shown that, majority of the undergraduates do not use the library resources in an expected level due to variety of anxieties.Therefore, the main aim of this paper is to assess and apply the Information seeking Anxiety Scale (ISAS) among university library users at University of Peradeniya and determines the suitability of application of this scale to a Sri Lankan university students relating to seeking of information.A survey research method was applied. Close-ended questionnaire was used as the research tool and data was collected from undergraduates in 2013/2014 academic year.The ISAS developed and validated by Mohammadamin, Abrizah and Karim, (2012) was taken as the base construct for this study. The overall a=0.902 of the original scale indicated and the Sri Lankan study increases up to 0.937. It indicates more or less similar results of the original study and it has been proved that, this scale can be applied to the Sri Lankan university context too. All the students are suffering with different types of anxieties related to the seeking of information. Therefore, it is better to have a year-based user education program for them to develop their skills to use resources without getting anxious.